Impact of climate change on food value of molluscs in Nepal - Subba, Bharat Raj (Nepalese Journal of Biosciences, 2013)
The questionnaires and interviews were taken randomly with ethnic people, the molluscs consumers of different districts of Tarai regions. Regarding other information about the impact of climate change in the context of Nepal, literature survey was done. Edible molluscs are cheap non-conventional source of protein for huge population of poor ethnic peoples (53 castes living in twenty districts of Tarai in Nepal), from time immemorial. Up to, nearly four and half decades back, there were virgin forests in Tarai region, water sources were in better condition but because of rapid population explosion, encroachment of wetlands and deforestation the water sources began to dry up early in the year. Gradual increase in atmospheric temperature due to imbalanced amount of CO2 and precipitation, is worsening the environment. The climate change is not only destroying the suitable aquatic environment of the molluscs habitats but their foods of plant and animal origins as well. Several changes in water chemistry might have taken place threatening aquatic lives including molluscs. As a result, annual production of mollusc also has decreased. The climate change is enforcing molluscs to change their original habitats and habits. While their production of molluscs is decreasing, demand is increasing due to rapid human population growth. The price of molluscs meat also has increased 100% as compared to one decade back (Bellamya Rs 20-25/kg with shell, Pila without shell Rs 48-60/kg, similarly bivalves (Lamellidens and Parreysia) Rs 20-30/kg with shell whereas Rs 50-60/kg without shell; Brotia Rs 10-12/kg with shell). Local production of Nepal covers hardly 30-40% demand of molluscs. The rest 60% demand is met imported from India. The only solution of the problem is to initiate molluscs culture which will also help conserve water sources and other aquatic organisms as well. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7496 Nepalese Journal of Biosciences 2 : 98-108 (2012)